Rereading Isaiah’s Vision (Isa 6) through the Lens of Generational Imprinted Trauma and Resilience - Groenewald, Alphonso 1969-; Esterhuizen, Elizabeth (2023)
In this contribution, the focus will be on the text of Isa 6:1-13 from the perspective of a generational imprinted trauma and resilience. This interdisciplinary approach renders a new conversation on Isaiah’s vision, not only giving scope to the ensuing traumatic events but also ascertaining hope and resilience that are embedded within the corpus of the chapter. These traumatic events and the possibility of hope expose the vulnerability of the prophet and the people of Judah within the complexity of the text. The aim of the contribution is to give an understanding of trauma, collective trauma and the possibility of hope as experienced within the prophet’s commission and vision as well as to investigate the impact that collective trauma has on the people. Thus, this article belongs in the domain of the literary and theological interpretation of the book of Isaiah and contributes towards the history of development of the book. The contribution will further aim to give an exegetical explanation of the structure of Isa 6 thereby giving a greater theological understanding of the text when using a lens of trauma and resilience. https://doi.org/10.17159/2312-3621/2023/v36n1a16